Application of in-situ gamma spectrometry for radiogenic heat production estimation in the Western Himalaya, Kohistan, and Karakoram in northern Pakistan - Muhammad Anees; Jonas Kley; Bernd Leiss; David Hindle; Ali Abbas Wajid; Bianca Wagner; Mumtaz M. Shah; Elco Luijendijk (Geothermal Energy, 2023)
Abstract The Himalaya, Kohistan, and Karakoram ranges comprise Proterozoic to Cenozoic crystalline complexes exposed in northern Pakistan. Numerous hot springs in the area indicate high subsurface temperatures, prompting a need to evaluate the local contribution of radiogenic heat to the general orogenic-related elevated geothermal gradients. The current study employed a portable gamma spectrometer to estimate the in-situ radiogenic heat production in the Nanga Parbat Massif, Kohistan–Ladakh batholith, and the Karakoram batholith. Heat production in the Nanga Parbat Massif is high, with a range from 0.2 to 10.8 µWm−3 and mean values of 4.6 ± 2.5 and 5.9 ± 1.9 µWm−3 for gneisses and granites, respectively. By contrast, the heat production is low in the Kohistan–Ladakh batholith, ranging from 0.1 to 3.1 µWm−3, with the highest mean of 2.0 ± 0.5 µWm−3 in granites. The Karakoram batholith shows a large variation in heat production, with values ranging from 0.4 to 20.3 µWm−3 and the highest mean of 8.4 ± 8.3 µWm−3 in granites. The in-situ radiogenic heat production values vary in different ranges and represent considerably higher values than those previously used for the thermal modeling of Himalaya. A conductive 1D thermal model suggests 93–108 °C hotter geotherms, respectively, at 10 and 20 km depths due to the thick heat-producing layer in the upper crust, resulting in a surface heat flow of 103 mWm−2. The present study provides first-order radiogenic heat production constraints for developing a thermal model for geothermal assessment.